Manchester triage system version II and resource utilisation in emergency department - Santos, A (2013)
Emergency department (ED) triage systems aim to direct the best clinical assistance to those who are in the greatest urgency and guarantee that resources are efficiently applied.The study's purpose was to determine whether the Manchester Triage System (MTS) second version is a useful instrument for determining the risk of hospital admission, intrahospital death and resource utilisation in ED and to compare it with the MTS first version.This was a prospective study of patients that attended the ED at a large hospital. It comprised a total of 25 218 cases that were triaged between 11 July and 13 October 2011. The MTS codes were grouped into two clusters: red and orange into a 'high acuity/priority' (HP) cluster, and yellow, green and blue into a 'low acuity/priority' cluster.The risk of hospital admission in the HP cluster was 4.86 times that of the LP cluster for both admission route and ages. The percentage of patient hospital admission between medical and surgical specialties, in high and low priority clusters, was similar. We found the risk of death in the HP cluster to be 5.58 times that of the risk of the low acuity/priority cluster. The MTS had an inconsistent association relative to the utilisation of x-ray, while it seemed to portray a consistent association between ECG and laboratory utilisation and MTS cluster.There were no differences between medical and surgical specialities risk of admission. This suggests that improvements were made in the second version of MTS, particularly in the discriminators of patients triaged to surgical specialties, because this was not true for the first version of MTS.